The importance of hologram technology in teaching high school students in Saudi Arabia schools in light of the Kingdom’s 2030 vision - Allhyani, Afaf Radi; Alotaibi, Engud Obaid (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the importance of the hologram technique in teaching high school students in the schools of Makah in the light of the Kingdom’s 2030 vision, and to achieve the goal of the study, the researcher used the descriptive analytical approach, and the questionnaire was used as a tool, and the study sample consisted of (68) secondary school teachers in the Kingdom’s schools Makah, in the academic year (1440 AH- 1441 AH), and one of the most important results of the study: The importance of the hologram technique in teaching secondary students in schools in the Kingdom of Makah in light of the Kingdom’s vision 2030 came in a great degree and with a percentage of 82.77% from the point of view of the teachers of the first stage In the secondary school and the existence of significant statistical differences(α = 0.05) is attributed to highly experienced teachers who have more than (10) years of experience. The findings did not show any statistically significant differences Attributed to the qualification.